The roles of osteocalcin in lipid metabolism in adipose tissue and liver. (December 2020) - Otani, Takahito; Mizokami, Akiko; Kawakubo-Yasukochi, Tomoyo; Takeuchi, Hiroshi; Inai, Tetsuichiro; Hirata, Masato
Abstract: Bone provides skeletal support and functions as an endocrine organ by producing osteocalcin, whose uncarboxylated form (GluOC) increases the metabolism of glucose and lipid by activating its putative G protein-coupled receptor (family C group 6 subtype A). Low doses (≤10 ng/ml) of GluOC induce the expression of adiponectin, adipose triglyceride lipase and peroxisome proliferator-activated receptor γ, and promote active phosphorylation of lipolytic enzymes such as perilipin and hormone-sensitive lipase via the cAMP-PKA-Src-Rap1-ERK-CREB signaling axis in 3T3-L1 adipocytes. Administration of high-dose (≥20 ng/ml) GluOC induces programmed necrosis (necroptosis) through a juxtacrine mechanism triggered by the binding of Fas ligand, whose expression is induced by forkhead box O1, to Fas that is expressed in adjacent adipocytes. Furthermore, expression of adiponectin and adipose triglyceride lipase in adipocytes is triggered in the same manner as following low-dose GluOC stimulation; these effects protect mice from diet-induced accumulation of triglycerides in hepatocytes and consequent liver injury through the upregulation of nuclear translocation of nuclear factor-E2-related factor-2, expression of antioxidant enzymes, and inhibition of the c-Jun N-terminal kinase pathway. Evaluation of these molecular mechanisms leads us to consider that GluOC might have potential as a treatment for lipid metabolism disorders. Indeed, there have been many reports demonstrating the negative correlation between serum osteocalcin levels and obesity or non-alcoholic fatty liver disease, a common risk factor for which is dyslipidemia in humans. The present review summarizes the effects of GluOC on lipid metabolism as well as its possible therapeutic application for metabolic diseases including obesity and dyslipidemia.